Tuning branching in ceria nanocrystals - Berestok, Taisiia; Guardia, Pablo; Blanco, Javier; Nafria, Raquel; Torruella, Pau; López Conesa, Luis; Estradé, Sònia; Ibanez Sabate, Maria; De Roo, Jonathan; Luo, Zhishan; Cadavid, Doris; Martins, José; et al. (Chemistry of Materials)
Branched nanocrystals (NCs) enable high atomic surface exposure within a crystalline network that provides avenues for charge transport. This combination of properties makes branched NCs particularly suitable for a range of applications where both interaction with the media and charge transport are involved. Herein we report on the colloidal synthesis of branched ceria NCs by means of a ligand-mediated overgrowth mechanism. In particular, the differential coverage of oleic acid as an X-type ligand at ceria facets with different atomic density, atomic coordination deficiency, and oxygen vacancy density resulted in a preferential growth in the [111] direction and thus in the formation of ceria octapods. Alcohols, through an esterification alcoholysis reaction, promoted faster growth rates that translated into nanostructures with higher geometrical complexity, increasing the branch aspect ratio and triggering the formation of side branches. On the other hand, the presence of water resulted in a significant reduction of the growth rate, decreasing the reaction yield and eliminating side branching, which we associate to a blocking of the surface reaction sites or a displacement of the alcoholysis reaction. Overall, adjusting the amounts of each chemical, well-defined branched ceria NCs with tuned number, thickness, and length of branches and with overall size ranging from 5 to 45 nm could be produced. We further demonstrate that such branched ceria NCs are able to provide higher surface areas and related oxygen storage capacities (OSC) than quasi-spherical NCs.

Disorder enabled band structure engineering of a topological insulator surface - Xu, Yishuai; Chiu, Janet; Miao, Lin; He, Haowei; Alpichshev, Zhanybek; Kapitulnik, Aharon; Biswas, Rudro; Wray, Lewis (Nature Communications)
Three-dimensional topological insulators are bulk insulators with Z 2 topological electronic order that gives rise to conducting light-like surface states. These surface electrons are exceptionally resistant to localization by non-magnetic disorder, and have been adopted as the basis for a wide range of proposals to achieve new quasiparticle species and device functionality. Recent studies have yielded a surprise by showing that in spite of resisting localization, topological insulator surface electrons can be reshaped by defects into distinctive resonance states. Here we use numerical simulations and scanning tunnelling microscopy data to show that these resonance states have significance well beyond the localized regime usually associated with impurity bands. At native densities in the model Bi2X3 (X=Bi, Te) compounds, defect resonance states are predicted to generate a new quantum basis for an emergent electron gas that supports diffusive electrical transport.

Ultrafast dynamics in the presence of antiferromagnetic correlations in electron doped cuprate La2 xCexCuO4±δ - Vishik, Inna; Mahmood, Fahad; Alpichshev, Zhanybek; Gedik, Nuh; Higgins, Joshu; Greene, Richard (Physical Review B)
We used femtosecond optical pump-probe spectroscopy to study the photoinduced change in reflectivity of thin films of the electron-doped cuprate La2-xCexCuO4 (LCCO) with dopings of x=0.08 (underdoped) and x=0.11 (optimally doped). Above Tc, we observe fluence-dependent relaxation rates that begin at a temperature similar to the one where transport measurements first show signatures of antiferromagnetic correlations. Upon suppressing superconductivity with a magnetic field, it is found that the fluence and temperature dependence of relaxation rates are consistent with bimolecular recombination of electrons and holes across a gap (2ΔAF) originating from antiferromagnetic correlations which comprise the pseudogap in electron-doped cuprates. This can be used to learn about coupling between electrons and high-energy (ω>2ΔAF) excitations in these compounds and set limits on the time scales on which antiferromagnetic correlations are static.

Origin of the exciton mass in the frustrated Mott insulator Na2IrO3 - Alpichshev, Zhanybek; Sie, Edbert; Mahmood, Fahad; Cao, Gang; Gedik, Nuh (Physical Review B)
We use a three-pulse ultrafast optical spectroscopy to study the relaxation processes in a frustrated Mott insulator Na2IrO3. By being able to independently produce the out-of-equilibrium bound states (excitons) of doublons and holons with the first pulse and suppress the underlying antiferromagnetic order with the second one, we were able to elucidate the relaxation mechanism of quasiparticles in this system. By observing the difference in the exciton dynamics in the magnetically ordered and disordered phases we found that the mass of this quasiparticle is mostly determined by its interaction with the surrounding spins.

Bounding helly numbers via betti numbers - Goaoc, Xavier; Paták, Pavel; Patakova, Zuzana; Tancer, Martin; Wagner, Uli (A Journey through Discrete Mathematics: A Tribute to Jiri Matousek)
We show that very weak topological assumptions are enough to ensure the existence of a Helly-type theorem. More precisely, we show that for any non-negative integers b and d there exists an integer h(b, d) such that the following holds. If F is a finite family of subsets of Rd such that βi(∩G)≤b for any G⊊F and every 0 ≤ i ≤ [d/2]-1 then F has Helly number at most h(b, d). Here βi denotes the reduced Z2-Betti numbers (with singular homology). These topological conditions are sharp: not controlling any of these [d/2] first Betti numbers allow for families with unbounded Helly number. Our proofs combine homological non-embeddability results with a Ramsey-based approach to build, given an arbitrary simplicial complex K, some well-behaved chain map C*(K)→C*(Rd).

QSGD: Communication-efficient SGD via gradient quantization and encoding - Alistarh, Dan-Adrian; Grubic, Demjan; Li, Jerry; Tomioka, Ryota; Vojnović, Milan
Parallel implementations of stochastic gradient descent (SGD) have received significant research attention, thanks to its excellent scalability properties. A fundamental barrier when parallelizing SGD is the high bandwidth cost of communicating gradient updates between nodes; consequently, several lossy compresion heuristics have been proposed, by which nodes only communicate quantized gradients. Although effective in practice, these heuristics do not always converge. In this paper, we propose Quantized SGD (QSGD), a family of compression schemes with convergence guarantees and good practical performance. QSGD allows the user to smoothly trade off communication bandwidth and convergence time: nodes can adjust the number of bits sent per iteration, at the cost of possibly higher variance. We show that this trade-off is inherent, in the sense that improving it past some threshold would violate information-theoretic lower bounds. QSGD guarantees convergence for convex and non-convex objectives, under asynchrony, and can be extended to stochastic variance-reduced techniques. When applied to training deep neural networks for image classification and automated speech recognition, QSGD leads to significant reductions in end-to-end training time. For instance, on 16GPUs, we can train the ResNet-152 network to full accuracy on ImageNet 1.8 × faster than the full-precision variant.

ZipML: Training linear models with end-to-end low precision, and a little bit of deep learning - Zhang, Hantian; Li, Jerry; Kara, Kaan; Alistarh, Dan-Adrian; Liu, Ji; Zhang, Ce (Proceedings of Machine Learning Research)
Recently there has been significant interest in training machine-learning models at low precision: by reducing precision, one can reduce computation and communication by one order of magnitude. We examine training at reduced precision, both from a theoretical and practical perspective, and ask: is it possible to train models at end-to-end low precision with provable guarantees? Can this lead to consistent order-of-magnitude speedups? We mainly focus on linear models, and the answer is yes for linear models. We develop a simple framework called ZipML based on one simple but novel strategy called double sampling. Our ZipML framework is able to execute training at low precision with no bias, guaranteeing convergence, whereas naive quanti- zation would introduce significant bias. We val- idate our framework across a range of applica- tions, and show that it enables an FPGA proto- type that is up to 6.5 × faster than an implemen- tation using full 32-bit precision. We further de- velop a variance-optimal stochastic quantization strategy and show that it can make a significant difference in a variety of settings. When applied to linear models together with double sampling, we save up to another 1.7 × in data movement compared with uniform quantization. When training deep networks with quantized models, we achieve higher accuracy than the state-of-the- art XNOR-Net.

Mitochondrial mutations and metabolic adaptation in pancreatic cancer - Hardie, Rae; Van Dam, Ellen; Cowley, Mark; Han, Ting; Balaban, Seher; Pajic, Marina; Pinese, Mark; Iconomou, Mary; Shearer, Robert; Mckenna, Jessie; Miller, David; Waddell, Nicola; et al. (Cancer & Metabolism)
Pancreatic cancer has a five-year survival rate of ~8%, with characteristic molecular heterogeneity and restricted treatment options. Targeting metabolism has emerged as a potentially effective therapeutic strategy for cancers such as pancreatic cancer, which are driven by genetic alterations that are not tractable drug targets. Although somatic mitochondrial genome (mtDNA) mutations have been observed in various tumors types, understanding of metabolic genotype-phenotype relationships is limited.

Structure of respiratory complex I: “Minimal” bacterial and “de luxe” mammalian versions - Sazanov, Leonid A (Mechanisms of primary energy transduction in biology)
Complex I (NADH:ubiquinone oxidoreductase) plays a central role in cellular energy generation, contributing to the proton motive force used to produce ATP. It couples the transfer of two electrons between NADH and quinone to translocation of four protons across the membrane. It is the largest protein assembly of bacterial and mitochondrial respiratory chains, composed, in mammals, of up to 45 subunits with a total molecular weight of ∼1 MDa. Bacterial enzyme is about half the size, providing the important “minimal” model of complex I. The l-shaped complex consists of a hydrophilic arm, where electron transfer occurs, and a membrane arm, where proton translocation takes place. Previously, we have solved the crystal structures of the hydrophilic domain of complex I from Thermus thermophilus and of the membrane domain from Escherichia coli, followed by the atomic structure of intact, entire complex I from T. thermophilus. Recently, we have solved by cryo-EM a first complete atomic structure of mammalian (ovine) mitochondrial complex I. Core subunits are well conserved from the bacterial version, whilst supernumerary subunits form an interlinked, stabilizing shell around the core. Subunits containing additional cofactors, including Zn ion, NADPH and phosphopantetheine, probably have regulatory roles. Dysfunction of mitochondrial complex I is implicated in many human neurodegenerative diseases. The structure of mammalian enzyme provides many insights into complex I mechanism, assembly, maturation and dysfunction, allowing detailed molecular analysis of disease-causing mutations.

Loschmidt echo in many body localized phases - Serbyn, Maksym; Abanin, Dimitry (Physical Review B - Condensed Matter and Materials Physics)
The Loschmidt echo, defined as the overlap between quantum wave function evolved with different Hamiltonians, quantifies the sensitivity of quantum dynamics to perturbations and is often used as a probe of quantum chaos. In this work we consider the behavior of the Loschmidt echo in the many-body localized phase, which is characterized by emergent local integrals of motion and provides a generic example of nonergodic dynamics. We demonstrate that the fluctuations of the Loschmidt echo decay as a power law in time in the many-body localized phase, in contrast to the exponential decay in few-body ergodic systems. We consider the spin-echo generalization of the Loschmidt echo and argue that the corresponding correlation function saturates to a finite value in localized systems. Slow, power-law decay of fluctuations of such spin-echo-type overlap is related to the operator spreading and is present only in the many-body localized phase, but not in a noninteracting Anderson insulator. While most of the previously considered probes of dephasing dynamics could be understood by approximating physical spin operators with local integrals of motion, the Loschmidt echo and its generalizations crucially depend on the full expansion of the physical operators via local integrals of motion operators, as well as operators which flip local integrals of motion. Hence these probes allow one to get insights into the relation between physical operators and local integrals of motion and access the operator spreading in the many-body localized phase.

Fluctuations of the competition interface in presence of shocks - Ferrari, Patrik; Nejjar, Peter (Revista Latino-Americana de Probabilidade e Estatística)
We consider last passage percolation (LPP) models with exponentially distributed random variables, which are linked to the totally asymmetric simple exclusion process (TASEP). The competition interface for LPP was introduced and studied in Ferrari and Pimentel (2005a) for cases where the corresponding exclusion process had a rarefaction fan. Here we consider situations with a shock and determine the law of the fluctuations of the competition interface around its deter- ministic law of large number position. We also study the multipoint distribution of the LPP around the shock, extending our one-point result of Ferrari and Nejjar (2015).

Spin it: Optimizing moment of inertia for spinnable objects - Bächer, Moritz; Bickel, Bernd; Whiting, Emily; Sorkine Hornung, Olga (Communications of the ACM)
Spinning tops and yo-yos have long fascinated cultures around the world with their unexpected, graceful motions that seemingly elude gravity. Yet, due to the exceeding difficulty of creating stably spinning objects of asymmetric shape in a manual trial-and-error process, there has been little departure from rotationally symmetric designs. With modern 3D printing technologies, however, we can manufacture shapes of almost unbounded complexity at the press of a button, shifting this design complexity toward computation. In this article, we describe an algorithm to generate designs for spinning objects by optimizing their mass distribution: as input, the user provides a solid 3D model and a desired axis of rotation. Our approach then modifies the interior mass distribution such that the principal directions of the moment of inertia align with the target rotation frame. To create voids inside the model, we represent its volume with an adaptive multiresolution voxelization and optimize the discrete voxel fill values using a continuous, nonlinear formulation. We further optimize for rotational stability by maximizing the dominant principal moment. Our method is well-suited for a variety of 3D printed models, ranging from characters to abstract shapes. We demonstrate tops and yo-yos that spin surprisingly stably despite their asymmetric appearance.

Ensembles of bidirectional kinesin Cin8 produce additive forces in both directions of movement - Fallesen, Todd; Roostalu, Johanna; Düllberg, Christian F; Pruessner, Gunnar; Surrey, Thomas (Biophysical Journal)
Most kinesin motors move in only one direction along microtubules. Members of the kinesin-5 subfamily were initially described as unidirectional plus-end-directed motors and shown to produce piconewton forces. However, some fungal kinesin-5 motors are bidirectional. The force production of a bidirectional kinesin-5 has not yet been measured. Therefore, it remains unknown whether the mechanism of the unconventional minus-end-directed motility differs fundamentally from that of plus-end-directed stepping. Using force spectroscopy, we have measured here the forces that ensembles of purified budding yeast kinesin-5 Cin8 produce in microtubule gliding assays in both plus- and minus-end direction. Correlation analysis of pause forces demonstrated that individual Cin8 molecules produce additive forces in both directions of movement. In ensembles, Cin8 motors were able to produce single-motor forces up to a magnitude of ∼1.5 pN. Hence, these properties appear to be conserved within the kinesin-5 subfamily. Force production was largely independent of the directionality of movement, indicating similarities between the motility mechanisms for both directions. These results provide constraints for the development of models for the bidirectional motility mechanism of fission yeast kinesin-5 and provide insight into the function of this mitotic motor.

Invasive Ameisen in Europa: Wie sie sich ausbreiten und die heimische Fauna verändern - Cremer, Sylvia (Rundgespräche Forum Ökologie)
The social insects bees, wasps, ants, and termites are species-rich, occur in many habitats, and often constitute a large part of the biomass. Many are also invasive, including species of termites, the red imported fire ant, and the Argentine ant. While invasive social insects have been a problem in Southern Europe for some time, Central Europa was free of invasive ant species until recently because most ants are adapted to warmer climates. Only in the 1990s, did Lasius neglectus, a close relative of the common black garden ant, arrive in Germany. First described in 1990 based on individuals collected in Budapest, the species has since been detected for example in France, Germany, Spain, England, and Kyrgyzstan. The species is spread with soil during construction work or plantings, and L. neglectus therefore is often found in parks and botanical gardens. Another invasive ant now spreading in southern Germany is Formica fuscocinerea, which occurs along rivers, including in the sandy floodplains of the river Isar. As is typical of pioneer species, F. fuscocinerea quickly becomes extremely abundant and therefore causes problems for example on playgrounds in Munich. All invasive ant species are characterized by cooperation across nests, leading to strongly interconnected, very large super-colonies. The resulting dominance results in the extinction of native ant species as well as other arthropod species and thus in the reduction of biodiversity.

Sexual-lineage-specific DNA methylation regulates meiosis in Arabidopsis - Walker, James; Gao, Hongbo; Zhang, Jingyi; Aldridge, Billy; Vickers, Martin; Higgins, James D.; Feng, Xiaoqi (Nature Genetics)
DNA methylation regulates eukaryotic gene expression and is extensively reprogrammed during animal development. However, whether developmental methylation reprogramming during the sporophytic life cycle of flowering plants regulates genes is presently unknown. Here we report a distinctive gene-targeted RNA-directed DNA methylation (RdDM) activity in the Arabidopsis thaliana male sexual lineage that regulates gene expression in meiocytes. Loss of sexual-lineage-specific RdDM causes mis-splicing of the MPS1 gene (also known as PRD2), thereby disrupting meiosis. Our results establish a regulatory paradigm in which de novo methylation creates a cell-lineage-specific epigenetic signature that controls gene expression and contributes to cellular function in flowering plants.
Keywords: Genetics

The RNA-binding protein tristetraprolin schedules apoptosis of pathogen-engaged neutrophils during bacterial infection - Ebner, Florian; Sedlyarov, Vitaly; Tasciyan, Saren; Ivin, Masa; Kratochvill, Franz; Gratz, Nina; Kenner, Lukas; Villunger, Andreas; Sixt, Michael K; Kovarik, Pavel (The Journal of Clinical Investigation)
Protective responses against pathogens require a rapid mobilization of resting neutrophils and the timely removal of activated ones. Neutrophils are exceptionally short-lived leukocytes, yet it remains unclear whether the lifespan of pathogen-engaged neutrophils is regulated differently from that in the circulating steady-state pool. Here, we have found that under homeostatic conditions, the mRNA-destabilizing protein tristetraprolin (TTP) regulates apoptosis and the numbers of activated infiltrating murine neutrophils but not neutrophil cellularity. Activated TTP-deficient neutrophils exhibited decreased apoptosis and enhanced accumulation at the infection site. In the context of myeloid-specific deletion of Ttp, the potentiation of neutrophil deployment protected mice against lethal soft tissue infection with Streptococcus pyogenes and prevented bacterial dissemination. Neutrophil transcriptome analysis revealed that decreased apoptosis of TTP-deficient neutrophils was specifically associated with elevated expression of myeloid cell leukemia 1 (Mcl1) but not other antiapoptotic B cell leukemia/ lymphoma 2 (Bcl2) family members. Higher Mcl1 expression resulted from stabilization of Mcl1 mRNA in the absence of TTP. The low apoptosis rate of infiltrating TTP-deficient neutrophils was comparable to that of transgenic Mcl1-overexpressing neutrophils. Our study demonstrates that posttranscriptional gene regulation by TTP schedules the termination of the antimicrobial engagement of neutrophils. The balancing role of TTP comes at the cost of an increased risk of bacterial infections.

Complex chromosomal neighborhood effects determine the adaptive potential of a gene under selection - Steinrück, Magdalena; Guet, Calin C (eLife)
How the organization of genes on a chromosome shapes adaptation is essential for understanding evolutionary paths. Here, we investigate how adaptation to rapidly increasing levels of antibiotic depends on the chromosomal neighborhood of a drug-resistance gene inserted at different positions of the Escherichia coli chromosome. Using a dual-fluorescence reporter that allows us to distinguish gene amplifications from other up-mutations, we track in real-time adaptive changes in expression of the drug-resistance gene. We find that the relative contribution of several mutation types differs systematically between loci due to properties of neighboring genes: essentiality, expression, orientation, termination, and presence of duplicates. These properties determine rate and fitness effects of gene amplification, deletions, and mutations compromising transcriptional termination. Thus, the adaptive potential of a gene under selection is a system-property with a complex genetic basis that is specific for each chromosomal locus, and it can be inferred from detailed functional and genomic data.

Green-light-induced inactivation of receptor signaling using cobalamin-binding domains - Kainrath, Stephanie; Stadler, Manuela; Gschaider-Reichhart, Eva; Distel, Martin; Janovjak, Harald L (Angewandte Chemie - International Edition)
Optogenetics and photopharmacology provide spatiotemporally precise control over protein interactions and protein function in cells and animals. Optogenetic methods that are sensitive to green light and can be used to break protein complexes are not broadly available but would enable multichromatic experiments with previously inaccessible biological targets. Herein, we repurposed cobalamin (vitamin B12) binding domains of bacterial CarH transcription factors for green-light-induced receptor dissociation. In cultured cells, we observed oligomerization-induced cell signaling for the fibroblast growth factor receptor 1 fused to cobalamin-binding domains in the dark that was rapidly eliminated upon illumination. In zebrafish embryos expressing fusion receptors, green light endowed control over aberrant fibroblast growth factor signaling during development. Green-light-induced domain dissociation and light-inactivated receptors will critically expand the optogenetic toolbox for control of biological processes.

An effective feedback loop between cell-cell contact duration and morphogen signaling determines cell fate - Barone, Vanessa; Lang, Moritz; Krens, Gabriel; Pradhan, Saurabh; Shamipour, Shayan; Sako, Keisuke; Sikora, Mateusz K; Guet, Calin C; Heisenberg, Carl-Philipp J (Developmental Cell)
Cell-cell contact formation constitutes an essential step in evolution, leading to the differentiation of specialized cell types. However, remarkably little is known about whether and how the interplay between contact formation and fate specification affects development. Here, we identify a positive feedback loop between cell-cell contact duration, morphogen signaling, and mesendoderm cell-fate specification during zebrafish gastrulation. We show that long-lasting cell-cell contacts enhance the competence of prechordal plate (ppl) progenitor cells to respond to Nodal signaling, required for ppl cell-fate specification. We further show that Nodal signaling promotes ppl cell-cell contact duration, generating a positive feedback loop between ppl cell-cell contact duration and cell-fate specification. Finally, by combining mathematical modeling and experimentation, we show that this feedback determines whether anterior axial mesendoderm cells become ppl or, instead, turn into endoderm. Thus, the interdependent activities of cell-cell signaling and contact formation control fate diversification within the developing embryo.

PirB regulates asymmetries in hippocampal circuitry - Ukai, Hikari; Kawahara, Aiko; Hirayama, Keiko; Case, Matthew J; Aino, Shotaro; Miyabe, Masahiro; Wakita, Ken; Oogi, Ryohei; Kasayuki, Michiyo; Kawashima, Shihomi; Sugimoto, Shunichi; Chikamatsu, Kanako; et al. (PLoS One)
Left-right asymmetry is a fundamental feature of higher-order brain structure; however, the molecular basis of brain asymmetry remains unclear. We recently identified structural and functional asymmetries in mouse hippocampal circuitry that result from the asymmetrical distribution of two distinct populations of pyramidal cell synapses that differ in the density of the NMDA receptor subunit GluRε2 (also known as NR2B, GRIN2B or GluN2B). By examining the synaptic distribution of ε2 subunits, we previously found that β2-microglobulin-deficient mice, which lack cell surface expression of the vast majority of major histocompatibility complex class I (MHCI) proteins, do not exhibit circuit asymmetry. In the present study, we conducted electrophysiological and anatomical analyses on the hippocampal circuitry of mice with a knockout of the paired immunoglobulin-like receptor B (PirB), an MHCI receptor. As in β2-microglobulin-deficient mice, the PirB-deficient hippocampus lacked circuit asymmetries. This finding that MHCI loss-of-function mice and PirB knockout mice have identical phenotypes suggests that MHCI signals that produce hippocampal asymmetries are transduced through PirB. Our results provide evidence for a critical role of the MHCI/PirB signaling system in the generation of asymmetries in hippocampal circuitry.